Circular RNA‐0072309 has antitumor influences in Hep3B cell line by targeting microRNA‐665. (11th February 2020) - Yu, Qiuyun; Dai, Jinhua; Shu, Ming
Abstract: Liver cancer is a malignant tumor that occurs in the liver and has a high mortality rate. We strived to detect the role and mechanism of circRNA‐0072309 in liver cancer. Hep3B cell line was transfected with pc‐circ and si‐circ for viability, colony formation, apoptosis, migration, and invasion tests, which were individually performed by CCK‐8, colony formation detection, flow cytometry assay, migration and invasion assays. What is more, the luciferase reporter assay was conducted to determine the target relationship between the circRNA‐0072309 and microRNA (miR)‐665. The expression of circRNA‐0072309 was examined by qRT‐PCR. The expression of proteins was examined via western blot. CircRNA‐0072309 was lowly expressed in liver cancer tissues and positively associated with 5‐year survival rate. The viability, colony formation, invasive and migratory ability were inhibited by abundant circRNA‐0072309, which promoted cell apoptosis on the contrary. CircRNA‐0072309 knockdown induced opposite effects, but could not affect apoptosis. Overexpressed miR‐665 in tumor tissues was targeted and negatively controlled by circRNA‐0072309. The PI3K/AKT and Wnt/β‐catenin pathways were inhibited by abundant circRNA‐0072309. miR‐665 overexpression disturbed those effects derived from pc‐circ. The circRNA‐0072309 had antitumor influences in Hep3B cell line through targeting miR‐665 relying on the deactivation of PI3K/AKT and Wnt/β‐catenin pathways.